The Cognizant of Allergy Diseases and Climate Change - Din, Norrina; Ramli, Kamal Izzuwan; Rashid, Basri (GATR Enterprise, 2013)
Objective – This paper discover about factors influencing food allergy knowledge and understanding. It also includes experience, training and information of food allergy as well as points out to the inadequate attentions is given to the allergy diseases that focus on food allergy risk outlets such as nurseries, schools and university food service establishments. Methodology/Technique – This paper review of literature review about allergy disease and climate change. Findings – This paper contributes to the understanding about the importance of food allergy awareness among public. Novelty – This paper discover about allergy disease and climate change to enhance public knowledge and awareness.